Multi-objective energy management in a micro-grid - Gholamreza Aghajani; Noradin Ghadimi (Energy Reports, 2018)
In recent years, the management and operation of micro-grids are considered by many advanced societies with regard to the development of scattered energy resources. The main goals that are paid attention in micro-grid management are the operation cost and pollution rate, which the aggregation of such contradictory goals in an optimization problem can provide an appropriate response to the management of the micro-grid. In this paper, the MOPSO method has been used for management and optimal distribution of energy resources in proposed micro-grid. On the other hand, the problem was analyzed with the NSGA-II algorithm to demonstrate the efficiency of the proposed method.
Keywords: 330; Energy management; Micro-grid; Multi-objective optimization; Renewable energy